Taxonomic revision of the North-African species of the genus Oiketicoides Heylaerts, 1881 (Lepidoptera: Psychidae: Oiketicinae) - Sobczyk, Thomas; Arnscheid, Wilfried R. (Zootaxa, 2021)
In this paper the North African species of the genus Oiketicoides Heylaerts, 1881, are revised. In total there are 16 species of which Oiketicoides algeriensis sp. nov., Oiketicoides albomaculatus sp. nov., Oiketicoides pseudochottella sp. nov., Oiketicoides numidicum sp. nov., Oiketicoides maroccensis sp. nov., Oiketicoides maghrebensis sp. nov., Oiketicoides imazigheni sp. nov. and Oiketicoides atlanticum sp. nov. are described here as new for science. The subspecies described as Oiketicoides febretta lambessa (Heylaerts, 1889) is treated here as belonging to the species rank and a lectotype is formally fixed.